A Peculiar Case of Invasive Streptococcus pneumoniae - Adeel Rafi Ahmed; Liam Townsend; Helen Tuite; Catherine Fleming (Case Reports in Infectious Diseases)
Patients commonly present to the emergency department with acute respiratory distress; however, the differentials are broad and at times difficult to distinguish. We describe a case of severe community-acquired pneumonia (CAP) secondary to invasive Streptococcus pneumoniae. The patient was intubated within 3 h of presentation and suffered multiorgan failure within 72 h of intensive care unit (ICU) admission. This case is a stark illustration of how the most common bacteria associated with CAP can be fatal and highlights the associated markers of severity. It also outlines other potential complications including a very rare phenomenon of cardiomyopathy with myocarditis associated with S. pneumoniae bacteraemia.